Learning Outcomes and ICT Integration: Techno Pedagogical Attitude of Primary School Teachers in Kannur District Kerala - Shafeek, P.; Hassankoya, M.P (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
During this post chalk-and-talk teaching scenario there need a hasty application of technology in the process of teaching and learning. To access this inevitable, which can only make easy to convey the learning outcomes to the digital students and education in leading position, attitude of teachers is a crucial thing. Techno pedagogy is the hybrid method of teaching in which ICT resources are applied in class room interaction practices. It is the art and craft of integrating technology in modifying teaching learning involvements in an active manner. Attaining techno-pedagogical competences will make teaching and learning a pleasant exercise as it would reduce the burden on the teachers and assist the students to dig deeper into realm of knowledge. The present studies try to understand the present attitude of teachers and to what extent it should be changed.